Trend of Technological Pedagogical Content Knowledge (TPACK) for Pre-service Science Teacher: A Historical Review (Jurnal Pendidikan Fisika, 2022)
Technological pedagogical content knowledge (TPACK) is critical for effective technology-enhanced education and has been increasing for several years. This research aims to provide a historical overview of TPACK-related studies for pre-service teachers, particularly those in the science department. The databases held 143 papers from 2012 to 2022, which were reviewed in four steps: identification, screening, eligibility, and inclusion, yielding 44 noteworthy articles on TPACK research. The meta-analysis design was utilized in the study, with the parameters of the study's purpose, method/design, sample, data collection, and location. According to the data, most studies measure pre-service teachers' TPACK using a variety of techniques and samples. And recently, the quantitative method has grabbed the lead. TPACK studies have grown in quantity over time, with the emphasis on measuring and enhancing pre-service teachers' TPACK. Despite the fact that the trend is increasing, the Indonesian context is still rare, and this study suggests that additional research into the TPACK environment in Indonesia is essential.
Keywords: historical review; pre-service teacher; science education; TPACK